Romance, Religion, and Recommendation: The Role of Algorithms in Shaping the Future of Digital Religious Fiction - Zulfa Fahmy; Teguh Supriyanto; Agus Nuryatin; Yusro Edy Nugroho (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study discusses the influence of digital platform algorithms on marketing strategies and readers' perception of religious romance novels in the era of platformization. The aim of the research is to explore the role of algorithms in the distribution of works, readers' responses to religious values in narratives, as well as relevant market strategies for religious romance novelists. The method used is a qualitative approach through content analysis and online surveys of Wattpad, Fizzo, and KBM App. Data was collected from popular texts, reader interactions, as well as responses to the themes and moral values featured in the story. The results show that the algorithm significantly affects the reach of the work. Writers who are active, consistently use tags, and build interactions get greater visibility. Readers appreciate the conflict between love and religious values, and make the novel a medium of spiritual reflection. This research recommends collaboration between authors, readers, and platforms to create an adaptive and inclusive religious literary ecosystem.